2021
DOI: 10.1101/2021.04.03.21254823
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A prospective observational safety study on ChAdOx1 nCoV-19 corona virus vaccine (recombinant) use in healthcare workers- first results from India

Abstract: Vaccines are an important public health measure for tiding over the COVID-19 pandemic. Several vaccines have been approved in different countries for emergency use. In India, two vaccines have been currently approved- COVISHIELD (Serum Institute of India (SII)) which is a recombinant simian adenovirus-based vaccine and COVAXIN (Bharat Biotech) which is an inactivated SARS-CoV-2 vaccine. Our current study provides the first post approval safety data on ChAdOx1 nCoV- 19 corona virus vaccine (recombinant) use in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 11 publications
(3 reference statements)
2
17
1
Order By: Relevance
“…The incidence rate of AEFIs reported within 30 min was 0.66%, and a similar result of 0.9% incidence was observed in a recent Indian study. 20 However, the overall incidence in this study 20 was as high as 40%, which is much higher than the incidence observed in the current study (3.48%). This might be due to the difference in the study method as the refereed study had followed up their beneficiaries in fixed time intervals for identifying the AEs, and they enrolled a smaller study population compared with our study.…”
Section: Discussioncontrasting
confidence: 76%
“…The incidence rate of AEFIs reported within 30 min was 0.66%, and a similar result of 0.9% incidence was observed in a recent Indian study. 20 However, the overall incidence in this study 20 was as high as 40%, which is much higher than the incidence observed in the current study (3.48%). This might be due to the difference in the study method as the refereed study had followed up their beneficiaries in fixed time intervals for identifying the AEs, and they enrolled a smaller study population compared with our study.…”
Section: Discussioncontrasting
confidence: 76%
“…Baseline demographic details of each participant were collected in a pre-designed case report form. 1 Enrollment was continued till the target sample size (n = 1650) was reached. As part of the ongoing prospective observational study, each participant is being monitored telephonically at specific intervals following the second dose, for a total duration of 1 year (study duration).…”
Section: Methodsmentioning
confidence: 99%
“…The authors recently demonstrated a favorable safety profile of COVISHIELD when assessed up to 7 days after the second dose. 1 Here, we report the preliminary findings regarding our secondary outcome measure of postvaccination SARS-CoV-2 infections. The data are based on at least 2 months of follow-up since the second dose of vaccine in enrolled participants who could be successfully contacted telephonically.…”
mentioning
confidence: 99%
“…The female participants were more because more nursing professionals were vaccinated in the first phase. Other studies reported 85.04%, 12 91.6% 14 , 57.24% 15 and 40% 13 AEFI after COVISHIELD vaccination. These findings vary in the higher and lower range compared to what we found.…”
Section: Discussionmentioning
confidence: 90%
“…14 Further another study found fever, headache, and dizziness were the commonly reported AEFIs, seen respectively in 15.2%, 6.2%, and 3.7% individuals. 13 Other studies found feeling unwell (19%), headache (17.4%), fever (12.5%), fatigue (12.3%), and muscle ache (11.2%). 17,18 Solicited injection-site pain was the most common local reaction, and fatigue and headache were the most common systemic reactions.…”
Section: Discussionmentioning
confidence: 91%